Enabling outdoor MR capabilities for head mounted displays: a case study. (7th January 2021) - Praschl, Christoph; Krauss, Oliver; Zwettler, Gerald A.
This research work covers generic approaches to determine the outdoor position and orientation of an augmented reality device due to the lack of outdoor capability of depth-sensor or environmental recognition-sensor-based devices currently available on the market. The determination of the orientation is primarily achieved with an attitude heading reference system (AHRS) for a rough estimation. Based on a connected/built-in video camera the accuracy at minor changes of the orientation is enhanced by applying registration to assess the differences in orientation between two video frames, compensating for gyroscope drift errors. The position determination is achieved using GPS with a rover and base station real time kinematic beacon system to achieve enhanced precision. Results show that due to sensor application AR hardware considered for indoor use can be retooled to properly work outdoors, at large distances and even inside running vehicles. Thus, future implementation of applications in various domains is facilitated.